Education in Inuit Nunangat: A Quantitative Examination of Factors Contributing to the Educational Attainments of Inuit - Pourfarzaneh, Sina (2020)
The literature identifies that Inuit lag behind the non-Inuit population in terms of education credentials. The gap in the rates of post-secondary education diplomas and degrees are even greater. Studies indicate that the lack of educational achievement by Inuit is mainly linked to the emergence of residential schools and its long-lasting destructive impacts in the Arctic. Moreover, the literature suggests that some deficiencies in Inuit Nunangat such as the absence of a university and lack of post-secondary education programs affect Inuit’s participation in advanced education. This research study uses data from the 2012 Aboriginal Peoples Survey to see how factors such as age, place of residence, the involvement of family members in education, first language learned in childhood, and residential school attendance contribute to the rate of attainment by Inuit in post-secondary education. The findings of this study reveal that, by age, the likelihood of having university education increases. Inuit who living outside of Inuit Nunangat are more likely to have post-secondary credentials. The involvement of family members in student education enhances the likelihood of having higher education achievements. Those Inuit who learned English as their first language in childhood are more likely to have completed advanced education. Finally, having the experience of attending residential schooling by the student or family members increases the likelihood of having university-level credentials.